Basic pharmacology : - Hernandez, Maria A. (CRC, Taylor & Francis, 2006)
The book provides an in-depth discussion of how to apply the chemical and molecular pharmacology concepts. This textbook introduces the principles of chemistry and biology necessary to understand drug interactions at the cellular level. The authors highlight chemical and physical properties of drugs, drug absorption and distribution, drug interactions with cellular receptors, and drug metabolism and elimination.